Citrus Blemishes and Decay Caused by Fungi and Bacteria - Mark A. Ritenour; Jamie D. Burrow; Megan M Dewdney; John Zhang (EDIS)
This is a quick identification tool of citrus blemishes and fruit decay caused by fungi and bacteria in Florida citrus.